Spiritualitas Tubuh sebagai Ekspresi Teologi Lokal melalui Pemujaan Dewa-Dewi dan Praktik Kebugaran dalam Rukmini Tattwa - Ni Made, Yunitha Asri Diantary (Jayapangus Press, 2025)
The body in the Hindu Balinese tradition is not only understood as a biological entity, but also as a sacred space that reflects the relationship between humans and divine power. Rukmini Tattwa as one of the important texts contains teachings about the sanctity of the body, worship of Gods and Goddesses, and fitness practices combined with spiritual discipline as a path to union with God. This study aims to reveal how the spirituality of the body and fitness practices are expressed as part of local Hindu Balinese theology through a study of rukmini tattwa and the accompanying ritual practices. The method used is qualitative with an approach of religious text study, symbolic analysis, and theological interpretation. Data were obtained through literature study, participatory observation, visual documentation, and in-depth interviews with religious figures and spiritual practitioners who were selected purposively. The results of the study show four main findings, namely 1) the body is seen as a sacred vessel (sarira) that must be cared for, 2) local Gods and Goddesses play a role in guiding religious awareness, 3) fitness practices in the form of yoga and body care are part of spiritual teachings, 4) interpretation of local theology that interprets the body as a medium of devotion. In conclusion, body spirituality is a real expression of local theology that is manifested through the care and purification of the body as a spiritual path.